Analisis Kedisiplinan Belajar Siswa Dalam Proses Pembelajaran Di Kelas VI SDN 2 Lemahtamba - Yuka, Vivi Vinara; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
One aspect considered very important for students in the school and classroom environment is discipline because it is related to the smooth teaching and learning process in the classroom. Discipline in schools is often associated with compliance and the orderliness of school residents in implementing the applicable rules. In this study, we will analyze the process of learning discipline that occurs in class VI SDN 2 Lemahtamba students during the learning process. The approach used in this research is qualitative. The method used is a case study aiming to determine the form of learning discipline in class VI, the factors that influence the process of learning discipline, and the efforts made in instilling learning discipline in students. This research, at the time of data collection, used interview techniques, observation guidelines, and documentation studies that support the research topic to be discussed. The results showed that most of the thirty students had done some form of discipline. However, only a few students were still doing activities that could interfere with learning activities during the learning process. It happened due to several factors that can come from within or outside the students themselves. The teacher has made various efforts to instill discipline in the classroom by making himself an excellent example of discipline in the school. So, researchers can conclude that the learning discipline process for class VI students at SDN 2 Lemahtamba is going quite well but lacks discipline because students still commit violations.